2015
DOI: 10.1111/jpy.12293
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic genes and sexual reproduction in the green algal class Trebouxiophyceae (Chlorophyta)

Abstract: Sexual reproduction is widespread in eukaryotes and is well documented in chlorophytan green algae. In this lineage, however, the Trebouxiophyceae represent a striking exception: in contrast to its relatives Chlorophyceae and Ulvophyceae this group appears to be mostly asexual, as fertilization has been rarely observed. Assessments of sexual reproduction in the Trebouxiophyceae have been based on microscopic observation of gametes fusing. New genomic data offer now the opportunity to check for the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 60 publications
(119 reference statements)
1
19
1
Order By: Relevance
“…The green algae Ostreoccoccus , Helicosporidium , and Chlorella , for which no sexual cycle is known, present the machinery for meiosis and the last two (Trebouxiophyceae) also present plasmogamy/mating types protein HAP2 (Trees, Supporting Information). Fučíková et al have previously reported similar results for the meiotic machinery for several unicellular green algae. We add to it the confirmation of HAP2 in Trebouxiophyceae; a mating type system may occur in this group.…”
Section: Sexuals and “Asexuals” Share The Same Meiotic Machinerysupporting
confidence: 56%
“…The green algae Ostreoccoccus , Helicosporidium , and Chlorella , for which no sexual cycle is known, present the machinery for meiosis and the last two (Trebouxiophyceae) also present plasmogamy/mating types protein HAP2 (Trees, Supporting Information). Fučíková et al have previously reported similar results for the meiotic machinery for several unicellular green algae. We add to it the confirmation of HAP2 in Trebouxiophyceae; a mating type system may occur in this group.…”
Section: Sexuals and “Asexuals” Share The Same Meiotic Machinerysupporting
confidence: 56%
“…is considered evidence for sexual reproduction (Schurko and Logsdon 2008). Also, in certain algae where sexual reproduction is very rarely observed (Trebouxiophyceae: Blanc et al 2010, Fučíková et al 2015, or has not yet been observed (Ostreococcus: Derelle et al 2006;Micromonas: Worden et al 2009), homologues of these core meiotic genes are present (Grimsley et al 2010).…”
Section: A Molecular Perspective On Fertility Genetic Controlmentioning
confidence: 99%
“…It includes the parabasalid Trichomonas vaginalis (43), the heterolobosean Naegleria gruberi (44), various trebouxiophyte green algae (45), Microsporidia (Opisthosporidia) (46), Glomeromycota (arbuscular mycorrhizal fungi) (47,48), and the naked foraminiferan Reticulomyxa filosa (Rhizaria) (49). It also comprises the amoeba Capsaspora owczarzaki, representing Filasterea, a small lineage related to multicellular animals and choanoflagellates, which have far more diverse proteins for cell adhesion and transcriptional regulation than encoded by the choanoflagellate genome (50).…”
Section: Sex In Eukaryotic Microorganisms: More Voyeurs Neededmentioning
confidence: 99%